Cadherins Glycans in Cancer: Sweet Players in a Bitter Process - Carvalho, S (2016)
Cadherins are key components in tissue morphogenesis and architecture, contributing to the establishment of cohesive cell adhesion. Reduced cellular adhesiveness as a result of cadherin dysfunction is a defining feature of cancer. During tumor development and progression, major changes in the glycan repertoire of cancer cells take place, affecting the stability, trafficking, and cell-adhesion properties of cadherins. Importantly, the different glycoforms of cadherins are promising biomarkers, with potential clinical application to improve the management of patients, and constitute targets for the development of new therapies. This review discusses the most recent insights on the impact of glycan structure on the regulation of cadherin function in cancer, and provides a perspective on how cadherin glycans constitute tumor biomarkers and potential therapeutic targets.